Pemberdayaan Ekonomi Rakyat Berbasis Pesantren di Kabupaten Hulu Sungai Utara - Surya Supi (JKAP (Jurnal Kebijakan dan Administrasi Publik), 2010)
Pesantren are widely spread in Indonesia reaching to the most remote areas, hence have the potential to empower people’s economy. Pesantren are involved in fostering self sufficiency among its members as well as the general society, which makes them a potential capital for empowering people’s economy. Using the integrity and capacity to mobilize resources. Pesantren are an important source in effort to increase community production and productivity. The study focused on two Pesantren Nurul Fajri of pesantren and Kholidiyah of pesantren located in Hulu Sungai Utara Regency, as example to evaluate the interchange and interactive between Islamic institutes / school and society. Society benefit from the existence of pesantren through various services and products of its business unit which contribute to solving their economic problems, contribute to community capital through the nurturing and promoting of cooperatives and employment. In addition, in the context capacity development, pesantren education contributes to community rejuvenation and society development, instill values and norm of hardworking, diligence, commitment, which vital for harmonious human existence, self actualization, and development.